Foreign experience of financial-legal and administrative legal regulation of the activities of public administration bodies - Leheza, Yevhen; Легеза, Євген; Kolomoiets, Yuliia; Коломоєць, Юлія Олександрівна; Kovalchuk, Yuliia; Ковальчук, Юлія; Sakhno, Artem; Сахно, Артем (UNIFOR-MG, 2024)
The purpose of the research is to consider financial and legal, administrative regulation and foreign experience of performing control over activities of public administration bodies. Main content. Defined are the main evaluation measures for ensuring effectiveness of control measures are defined; this evaluation is carried out according to the following stages: determination of quantitative and qualitative parameters for evaluating effectiveness of control; assessment of the competence of control bodies or assessment of internal and external control effectiveness, etc. Methodology: The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method as well as methods of analysis and synthesis. Conclusions. The following conclusion has been made that the following criteria are proposed for evaluating effectiveness of controlling public administration bodies: quality and completeness, reliability of information received by the controlling bodies; timeliness of control, regularity of control, objectivity of control, lightness of control measures. Метою дослідження є розгляд фінансово-правового, адміністративного регулювання та зарубіжного досвіду здійснення контролю за діяльністю органів державного управління. Основний зміст. Визначено основні оціночні заходи для забезпечення ефективності заходів контролю; ця оцінка здійснюється за такими етапами: визначення кількісних та якісних параметрів оцінки ефективності контролю; оцінка компетентності органів контролю або оцінка ефективності внутрішнього та зовнішнього контролю тощо. Методологія: Методологічною основою дослідження є порівняльно-правовий та системний аналіз, формально-юридичний метод, метод інтерпретації, герменевтичний метод, а також методи аналізу та синтезу. Висновки. Зроблено висновок про те, що для оцінки ефективності контролюючих органів державного управління пропонуються такі критерії: якість та повнота, достовірність інформації, що надходить до контролюючих органів; своєчасність контролю, регулярність контролю, об'єктивність контролю, легкість контрольних заходів.
Зарубіжний досвід фінансово-правового та адміністративно- правового регулювання діяльності органів державного управління
Keywords: administrative and legal principles; адміністративно-правові принципи; foreign experience; закордонний досвід; control; контроль; public administration bodies; органи державного управління; financial and legal regulation; фінансово-правове регулювання